Effect of the Combination of the Growth Regulators and Putrescine on the Somatic Embryogenesis of Wheat (Triticum Aestivum L.) on Some Types of Explants - Yusniwati, Yusniwati; Setiawan, Ryan Budi (Green Engineering Society, 2023)
Plant breeding programs need to be carried out in order to improve the genetics of wheat that is able to adapt to tropical environments through hybridization, mutation induction, tissue culture, and genetic transformation. In vitro culture through somatic embryogenesis pathways plays an important role in genetic improvement and its integration with other breeding programs can positively affect the improvement of wheat quality, quantity, and development in Indonesia. The purpose of this study was to obtain an embryogenic callus induction method from the Dewata variety using five different types of explants, namely mature Seeds, immature embryos, immature seeds, leaf, stem, and to obtain combination of plant growth regulators and putrescine on somatic embryogenesis of wheat. The experimental design was prepared based on a complete randomized design with a combination treatment of embryogenic callus induction media consisting of 9 levels, namely: 1 ppm 2.4- D, 1 ppm 2.4-D + 1 ppm Picloram, ppm 2.4-D + 1 mg / L Picloram, 1 ppm 2.4-D + 10-4 M Putrescine, 1 ppm 2.4-D + 1 ppm Picloram +10-4 M Putrescine, 2 ppm 2.4-D + 1 ppm Picloram + 10-4 M Putrescine, 1 ppm 2.4 D + 10-3 M Putrescine, 1 ppm 2.4 D + 1 ppm Picloram + 10-3 M Putrescine, 2 ppm 2.4 D + 1 ppm Picloram + 10-3 M Putrescine. The results showed that the media used was able to induce embryogenic callus using mature seed and immature embryo, but immature seed and leaf were not able to produce embryogenic callus. The best media that produced the highest percentage of embryogenic callus was 2 ppm 2.4-D + 1 ppm Picloram + 10-4 M Putrescine with as much as 85.9% in young embryo explants.